If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(y-7)=2y-44
We move all terms to the left:
7(y-7)-(2y-44)=0
We multiply parentheses
7y-(2y-44)-49=0
We get rid of parentheses
7y-2y+44-49=0
We add all the numbers together, and all the variables
5y-5=0
We move all terms containing y to the left, all other terms to the right
5y=5
y=5/5
y=1
| -g=2+g | | 5(2x-1)-5x=-20+4x | | 7(y-7)=2y=44 | | h=-6+2/33 | | 3(10-x)=60-6 | | 61=7−6x | | /p-10=5 | | 5x+7=3x+4+3x+4 | | 4s=7+3s | | 750*0.12=o/120*750 | | 8x-3x+2=-53 | | 5p–6+p=14–2p | | 20=-3x^2+75 | | 0.8t-2=8 | | (1/z+8)-(1/z)=1/6 | | 117=2(2x-7) | | 3=z/13 | | x/3+2=0X | | 5r=-r-6 | | -33h=200 | | 9x-15=39x | | 8x2-32x+14=0 | | 4(x-5)=20-6x | | -2x-5=x-7 | | 226=14(v+11)+14 | | 3x+2x+5x=180-2x | | 180-2x+204=54 | | x-76=6(2x+3)-6 | | 3(x-7)=15+3x | | 1.5x+20=2 | | 117÷d=13 | | 2{x+5}=18 |